An Analysis of the Effect of Price and Quality on Customer Buying Patterns: An Empirical Study of iPhone Buyers - Maisarah Hamizan; Noor Hidayah Abu; Mohd Fitri Mansor; Mohd Azian Zaidi (International Journal of Interactive Mobile Technologies (iJIM), 2023)
Companies make use of various strategies in order to attract new customers, retain existing customers, and differentiate their products from those of their competitors. Apple Inc. is a multinational technology company headquartered in Cupertino, California. The company specializes in consumer devices, software, and online services. Apple is the most valuable firm in the world, the fourth-largest vendor of personal computers by unit sales, and the second-largest producer of mobile phones as of May 2022. The iPhone is a product with a strong reputation. Apple has always maintained product quality and continuously made innovations. The iPhone has a unique design, and in view of that, the model is too expensive compared to other mobile phones. Although the price is expensive, demand for the iPhone still increases from time to time. The aim of this research is to understand the factors behind iPhone purchase decisions. An investigation has been conducted to evaluate the relationship between price and quality on customer buying patterns for an iPhone. This study will adopt quantitative methods, and data collection has been conducted through online questionnaire distribution. The target respondents in this study are STML students, and the overall population of STML was 1645 students; thus, the sample size for the study should be 310 respondents. The cluster sampling technique has been used in this study. In this study, a total of 340 respondents were received, and there are 27 missing values in the data set. However, only 313 respondents are valid for the data analysis. Findings revealed that price and quality have a significant effect on the buying pattern of an iPhone. Lastly, this study discusses the limitations of the study and its conclusion.